2012
DOI: 10.1007/s10517-012-1809-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peripheral μ, δ, and κ-Opioid Receptor Agonists on the Levels of Anxiety and Motor Activity of Rats

Abstract: The effects of intragastric administration of μ-, δ, and Κ-opioid receptor agonists DAMGO, DADLE, and ICI 204,448, respectively, on the anxiety and motor activity of rats in an elevated plus-maze were studied. Peripheral administration of ICI 204,448 produced an anxiolytic effect, but had no effect on motor activity of rats. DAMGO and DADLE reduced motor activity; DADLE also increased anxiety. The data on the opposite effects of ICI 204,448 and DADLE on anxiety confirmed our previous hypothesis on the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…Moreover, social status also contribute to the behavioral responses observed following KOR activation in adults (Kudryavtseva et al, 2006). Although few studies have examined the behavioral effects of KOR activation in adolescents, all of them have shown that KOR agonists are anxiolytic in stress- and drug-naïve younger animals (Alexeeva et al, 2012; Braida et al, 2009; Privette and Terrian, 1995), particularly when infused in specific brain structures, such as the infralimbic cortex (Wall and Messier, 2000). Furthermore, adolescents display reduced aversion to systemic injections of KOR agonists (Anderson et al, 2014; Tejeda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, social status also contribute to the behavioral responses observed following KOR activation in adults (Kudryavtseva et al, 2006). Although few studies have examined the behavioral effects of KOR activation in adolescents, all of them have shown that KOR agonists are anxiolytic in stress- and drug-naïve younger animals (Alexeeva et al, 2012; Braida et al, 2009; Privette and Terrian, 1995), particularly when infused in specific brain structures, such as the infralimbic cortex (Wall and Messier, 2000). Furthermore, adolescents display reduced aversion to systemic injections of KOR agonists (Anderson et al, 2014; Tejeda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The number of lever pressings for obtaining one food granule was daily increased in a certain sequence (1,2,4,8,16, and 32) over 6 experimental days, respectively. Beyond the experimental situation (1-h testing), the animals had a restricted access to food (8 g standard combined feed per day).…”
Section: Methodsmentioning
confidence: 99%
“…Vagal afferentation transmits information on activation of μ-opioid receptors (OR) into CNS, which is followed by suppression of the central endogenous opioid system. These changes are accompanied by inhibition of feeding behavior [1]. However, little is known about the effect of peripheral agonists of various subtypes of OR on LFM.…”
mentioning
confidence: 99%
“…It was hypothesized that consumption of large volumes of ethanol-containing solutions induces pathophysiological changes in peptide systems regulating blood volume [7] and appetite [5]. The lastnamed system also includes opioid peptides [8,11].Our previous studies showed that changes in activity of some receptors in the stomach can modulate the pain sensitivity [4], locomotor activity [2], and level of anxiety in rats [1,3]. It cannot be excluded that gastric distention of various degrees affects the affinity and bioavailability of receptors.…”
mentioning
confidence: 99%
“…Our previous studies showed that changes in activity of some receptors in the stomach can modulate the pain sensitivity [4], locomotor activity [2], and level of anxiety in rats [1,3]. It cannot be excluded that gastric distention of various degrees affects the affinity and bioavailability of receptors.…”
mentioning
confidence: 99%